Service Quality to the Level of Customer Satisfaction and Loyalty at Banking in Surabaya Using the SEM Method: Kualitas Layanan hingga Tingkat Kepuasan dan Loyalitas Pelanggan di Perbankan di Surabaya Menggunakan Metode SEM - Yuniar Farida; Fithrotun Nadiyah; Hani Khaulasari (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2025)
Service quality in the banking sector has become a primary focus to ensure customer satisfaction and loyalty. This study aims to analyze the influence of service quality on customer satisfaction, customer satisfaction on customer loyalty, and service quality on customer loyalty at the Banking in Surabaya Branch. The sample obtained from the questionnaire consists of 160 customers. The data analysis technique used in this study is the SEM method, which analyzes the relationships between variables in a model. The SEM method also includes the role of a mediating variable, which is customer satisfaction, between service quality and customer loyalty. The results of this study indicate that service quality significantly impacts customer satisfaction, and customer satisfaction also significantly influences customer loyalty. Additionally, service quality has a direct impact on customer loyalty. Moreover, service quality indirectly affects customer loyalty through the mediating variable of customer satisfaction at the Banking in Surabaya Branch. The benefits of this research include developing business strategies for competitive advantage and strengthening the relationship between customers.